2011
DOI: 10.1073/pnas.1101405108
|View full text |Cite
|
Sign up to set email alerts
|

Activity of abundant and rare bacteria in a coastal ocean

Abstract: The surface layer of the oceans and other aquatic environments contains many bacteria that range in activity, from dormant cells to those with high rates of metabolism. However, little experimental evidence exists about the activity of specific bacterial taxa, especially rare ones. Here we explore the relationship between abundance and activity by documenting changes in abundance over time and by examining the ratio of 16S rRNA to rRNA genes (rDNA) of individual bacterial taxa. The V1-V2 region of 16S rRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
515
4
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 520 publications
(570 citation statements)
references
References 40 publications
38
515
4
13
Order By: Relevance
“…The experimental evaluation suggests that the quantification of functional genes by qPCR was mostly in agreement with the pyrosequencing of complex microbial communities. This study showed that rare taxa (mainly specialists), especially in the anoxic zone, cannot solely be characterized as a seed bank or dormant cells in Lake Kivu but that a significant portion of the rare community is potentially active, which supports the results of various studies conducted in freshwater and marine environments [13,14]. However, the impact of environmental parameters measuredwas stronger for the generalists (mainly abundant taxa), which indicates the presence of different ecological rules for different groups.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The experimental evaluation suggests that the quantification of functional genes by qPCR was mostly in agreement with the pyrosequencing of complex microbial communities. This study showed that rare taxa (mainly specialists), especially in the anoxic zone, cannot solely be characterized as a seed bank or dormant cells in Lake Kivu but that a significant portion of the rare community is potentially active, which supports the results of various studies conducted in freshwater and marine environments [13,14]. However, the impact of environmental parameters measuredwas stronger for the generalists (mainly abundant taxa), which indicates the presence of different ecological rules for different groups.…”
Section: Resultssupporting
confidence: 81%
“…In contrast, rare OTUs were detected in a high proportion exclusively in either bulk or potentially active bacterial communities. As suggested for estuarine and coastal ocean waters, the metabolically active rare biosphere of Lake Kivu might be potentially important for the functioning and the temporal dynamics of microbial communities as they shift between seasons [13][14][15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A Mantel test confirmed strong correlations between DNA and RNA-based BC compositions at all phylogenetic levels (Po0.01; Supplementary Table S4), similar to a previous report on samples collected off the US-American east coast (Campbell et al, 2011). Bacteria of the orders Flavobacteriales and Rhodobacterales were the most abundant taxa.…”
Section: Dom-bacteria Associations In the North Sea H Osterholz Et Alsupporting
confidence: 64%
“…Calculated rarefaction curves, as well as diversity indices (data not shown), revealed that our surveying effort discovered the majority of-yet not all-the bacterial species and phyla (480%) at 3% and 20% genetic distance. The active community yielded a higher number of OTUs than the total BC, resulting in a DNA/RNA ratio of OTU richness ranging from 0.76 to 0.88 and denoting that a significant portion of the rare taxa may be proportionally more active (Jones and Lennon, 2010;Campbell et al, 2011;Wilhelm et al, 2014). The percentage of OTUs that appeared in both, the RNA …”
Section: Bc Compositionmentioning
confidence: 99%